SISTEM INFORMASI PROMOSI WISATA BERBASIS WEB DI RUMAH PENGASINGAN BUNG KARNO - Fadlin, Mohamad (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Historic sites are a form of heritage and cultural heritage that have value for the present and future life of the nation. Ende City is one of the cities that has historical sites that have not been optimally managed. In this study, the design and construction of a Web-Based Tourism Promotion Information System at the Bung Karno Exile House was carried out. The problem found is that the service at the Bung Karno site is still inadequate, visitors who come often do not get clearer information about historical items on the Bung Karno site because there are no tour guides, there are only guards who sometimes cannot explain in detail about the historic item. Through the information system that has been built aims to provide convenience in finding information and data information accessed by visitors. Collecting data in this study using the method of literature study, observation and interviews. This study uses the Waterfall method by following the various stages in it. In this study, the test was also carried out using the Black Box method. The results of this study indicate that there is still a lack of information system implementation on the Bung Karno site and it is still very manual. The conclusion is, with the application of a Web-Based Tourism Promotion information system, it is hoped that it can help and make it easier for visitors or the public who want to visit the Bung Karno Site and also make it easier for officers to deal with problems such as schedules for the public or other visitors who come to visit. Key words: Bung Karno Site, Information System, Waterfall, Black Box.